1985
DOI: 10.3171/jns.1985.62.3.0389
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of the brain in treatment of chronic pain

Abstract: Forty-eight patients underwent electrical stimulation of the brain for treatment of chronic pain between 1978 and 1983. Average pain duration prior to treatment was 4.5 years. Before selection for this procedure patients underwent pain treatment in a multidisciplinary pain center, intensive psychological and psychiatric evaluation, and assessment of pain responsiveness to intravenous administration of placebo, morphine, and naloxone. A total of 71 electrodes were placed in the 48 patients at a variety of stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(51 citation statements)
references
References 27 publications
0
50
0
1
Order By: Relevance
“…The authors reviewed five case series and found that just 36 out of 334 patients benefitted from implanted DBS. 28,33,47,50,51 It should be noted that the nature or characteristics of the neuropathic pain in these patients was not described. In four studies with a total of 266 implantations, 80 major adverse events were reported that required 63 new surgical procedures.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reviewed five case series and found that just 36 out of 334 patients benefitted from implanted DBS. 28,33,47,50,51 It should be noted that the nature or characteristics of the neuropathic pain in these patients was not described. In four studies with a total of 266 implantations, 80 major adverse events were reported that required 63 new surgical procedures.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…In the following decades, electrical stimulation of the thalamus, internal capsule, and periaqueductal gray matter or periventricular gray matter (PVG) became commonly used procedures to treat chronic refractory pain. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Within the last decade, the number of patients with chronic pain treated with DBS, as well as the number of the published studies, have progressively decreased, mainly because of the lack of solid scientific evidence of DBS safety and efficacy and the development of less invasive alternatives to manage nociceptive pain. Although DBS produced impressive results in a subset of patients, the results were highly variable, and appropriate patient selection seems to be very important.…”
mentioning
confidence: 99%
“…In humans, stimulation of the PAG was originally applied for pain relief , Young, et al, 1985. Some studies also reported other findings after PAG stimulation.…”
mentioning
confidence: 89%
“…DBS for chronic pain has been undertaken for over half a century [15,16,17,18,19,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41], its use preceding the ‘gate theory' by a decade. However, multiple reports had conveyed an overall impression regarding DBS for pain that had led most neurosurgeons to abandon the technique [15,41].…”
Section: Discussionmentioning
confidence: 99%